Media Loose Parts to Improve The Operability of Children Aged 5-6 Years - Eneng Sri Susilawati; Siti Bariyah; Suci Aprilyati Ruiyat; Uswatun Khsanah (JTP - Jurnal Teknologi Pendidikan, 2026)
This study aims to improve the ability of number operations in group B children in the Parakanlima Play Group through the implementation of loose parts media. Number operation capabilities are fundamental mathematical concepts that include addition, subtraction, many-bit concepts, and the ability to connect concepts with number symbols. The research used the Kemmis and Taggart model Class Action Research (PTK) which was carried out in 2 cycles with 4 actions per cycle each. The subjects of the study were 20 children of group B aged 5-6 years consisting of 11 boys and 9 girls. Data collection techniques use observation, interviews, and documentation, with data analysis carried out qualitatively and quantitatively. The loose parts used include natural materials (pebbles, tree branches, leaves, flowers) and used items (bottle caps, shells, ice cream sticks, straws). The results showed a significant increase in the operating ability of children from pre-cycle by 44.68%, increased to 66.25% in cycle I, and reached 84.68% in cycle II, with a total increase of 40%. Improvement occurs in all aspects of number operations: addition (50% to 70%), many-bit concepts (45% to 65%), subtraction (40% to 60%), and associating concepts with number symbols (55% to 75%). Research proves that the implementation of loose parts media can effectively improve children's number operation skills through concrete, meaningful, and fun learning, so that the abstract concept of number operations becomes easy for children to understand. Media loose parts provide a hands-on experience that facilitates multi-sensory stimulation and encourages active learning.